Рассказы - Резин Михаил Семенович (Национальная библиотека Удмуртской Республики, 2017)
Экземпляры: БС (20180307) / Инвентарный номер: РТШ54663 / Сис.шифр: Р2 / Авт.знак: Р 34 / ГРНТИ: 17.82.32 / ББК: 84(2)